Category "event" and "event series" in the system of literary coordinates (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is devoted to definingthe basics of forming a literary category «event» and «event series». In addition, the text illustrated the essence, the types, the features, the functions of the category «event» that based on analysis of the works of the scientists different time.The author states that the literary researches of the category «event» are particularly relevant today.
Keywords: event; event series; perepetia; the literature category «event»; the event in literature